Activation of the viral sensor oligoadenylate synthetase 2 (Oas2) prevents pregnancy-driven mammary cancer metastases - Wing-Hong Jonathan Ho; Andrew M. K. Law; Etienne Masle-Farquhar; Lesley E. Castillo; Amanda Mawson; Moira K. O’Bryan; Christopher C. Goodnow; David Gallego-Ortega; Samantha R. Oakes; Christopher J. Ormandy (Breast Cancer Research, 2022)
Abstract Background The interferon response can influence the primary and metastatic activity of breast cancers and can interact with checkpoint immunotherapy to modulate its effects. Using N-ethyl-N-nitrosourea mutagenesis, we found a mouse with an activating mutation in oligoadenylate synthetase 2 (Oas2), a sensor of viral double stranded RNA, that resulted in an interferon response and prevented lactation in otherwise healthy mice. Methods To determine if sole activation of Oas2 could alter the course of mammary cancer, we combined the Oas2 mutation with the MMTV-PyMT oncogene model of breast cancer and examined disease progression and the effects of checkpoint immunotherapy using Kaplan–Meier survival analysis with immunohistochemistry and flow cytometry. Results Oas2 mutation prevented pregnancy from increasing metastases to lung. Checkpoint immunotherapy with antibodies against programmed death-ligand 1 was more effective when the Oas2 mutation was present. Conclusions These data establish OAS2 as a therapeutic target for agents designed to reduce metastases and increase the effectiveness of checkpoint immunotherapy.